Differential regulation of protein kinase C activity by modulating factors and Euonymus alatus (Thunb.) Sieb in human myometrial and uterine leiomyomal smooth muscle cells. Issue 2 (1st February 2005) - Lee, T.-K.; Lee, J.-Y.; Kim, D.-I.; Lee, Y.-C.; Kim, C.-H.
Abstract : Human myometrial smooth muscle cells (MSMC) showed high protein kinase C (PKC) activity when a maximal dose of PKC-activating phorbol ester was used, while uterine leiomyomal cells (ULMC) showed only 6–12% of PKC activity. MSMC exhibited a low proliferation rate, whereas ULMC exhibited a high proliferation rate. These different cell types of MSMC and ULMC responded to 10 U/mL thrombin, with a twofold stimulation of PKC activity. Downregulation of PKC activity was found when MSMC were treated with phorbol ester or with transforming growth factor-β2. We concluded that differences in PKC activity exist between MSMC and ULMC, which may be related to their different proliferative activity. ULMC treated with Euonymus alatus (Thunb.) Sieb (EA), known as "gui-jun woo" in Korea, which is used for leiomyomal tumors, exhibited a much lower proliferation rate than untreated cells, suggesting that EA inhibited the cellular proliferation of ULMC. The PKC activity of MSMC by EA treatment (50 μg/mL) changed little. ULMC showed increased PKC activity by addition of EA, indicating that PKC is activated by EA. The EA-treated ULMC were differentiated into phenotypes characteristic for normal untransformed cells, since the EA-treated cells possess higher PKC activity than untreated cells.